Thiocarbonyl-enabled ferrocene C–H nitrogenation by cobalt(III) catalysis: thermal and mechanochemical - Yetra, Santhivardhana Reddy; Shen, Zhigao; Wang, Hui; Ackermann, Lutz (Beilstein Journal of Organic Chemistry, 2018)
Versatile C–H amidations of synthetically useful ferrocenes were accomplished by weakly-coordinating thiocarbonyl-assisted cobalt catalysis. Thus, carboxylates enabled ferrocene C–H nitrogenations with dioxazolones, featuring ample substrate scope and robust functional group tolerance. Mechanistic studies provided strong support for a facile organometallic C–H activation manifold.
Keywords: amidation; C–H activation; cobalt; ferrocene; mechanochemistry